Upaya Perlindungan Hukum bagi Nasabah Asuransi oleh Negara dan Iktikad Baik dalam Alternatif Penyelesaian Sengketanya - Solihin Makmur Alam; Christin Septina Basani (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
The insurance industry, as a sub-system of the financial industry, is strictly regulated by regulators because insurance collects public funds in the form of premiums and then distributes them again when claims arise in the future. Despite strict regulations, in reality, the rights of insurance customers are often violated. Based on this, the purpose of this study is to examine what and how the state provides legal protection for insurance customers and good faith in alternative dispute resolution, with a scope covering solvent and insolvent insurance companies. The research method used is normative juridical. Legal protection efforts can be preventive and repressive. Preventive efforts before a dispute occurs include strengthening regulations, tightening guidance and supervision of the insurance industry, and providing education and socialization to customers and the public. Repressive measures after a dispute occurs are provided through court decisions, which are pursued by customers through legal action. Repressive measures are also provided by the authorities through written warnings, administrative sanctions in the form of restrictions/freezing of business activities or fines, revocation of business licenses, and conducting criminal investigations in the insurance sector. ADR (Alternative Dispute Resolution) is a legal effort outside of court facilitated by LAPS-SJK (Alternative Dispute Resolution Institution – Financial Services Sector) which, since 01 January 2021, has replaced BMAI (Indonesian Insurance Mediation and Arbitration Agency). Good faith on the part of insurance policyholders and insurance companies is essential in ADR. The enactment of the UUP2SK (Law on the Development and Strengthening of the Financial Services Sector), which delegates the LPS (Deposit Insurance Agency) as the LPP (Policy Guarantee Agency) as mandated by Article 53 of Law 40/2014 on Insurance, is an effort by the state to protect insurance customers from insolvent insurance companies.